2015
DOI: 10.17503/agrivita-2015-37-1-p008-017
|View full text |Cite
|
Sign up to set email alerts
|

Progress From Selection of Some Maize Cultivars’ Response to Drought in the Derived Savanna of Nigeria

Abstract: Field experiments were conducted to investigate the variations in sixteen maize genotypes in relation to drought tolerance. The experimental set up was subjected to drought stress after five weeks of planting for three weeks before data on morphological and yield characters of maize genotypes were obtained for three cropping years. Plant height and grain yield of Bodija yellow maize were the highest overall. There was a significant difference among genotypes for drought stress resistance and Bodija yellow maiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 10 publications
8
11
0
Order By: Relevance
“…Appropriately, this result depicted that expected progress from the selection of the cultivars is between 16.1 % (days to anthesis) and 51.8 % (capsule yield). This substantiates with the findings of Olawuyi et al (2015) and Hazem et al (2013).…”
Section: Resultssupporting
confidence: 92%
“…Appropriately, this result depicted that expected progress from the selection of the cultivars is between 16.1 % (days to anthesis) and 51.8 % (capsule yield). This substantiates with the findings of Olawuyi et al (2015) and Hazem et al (2013).…”
Section: Resultssupporting
confidence: 92%
“…This is an indication of genetic variability which exists among characters as previously reported by Olawuyi et al (2015), and Olawuyi et al (2016) and Agbolade et al (2016). This character could be further considered in mutation breeding.…”
Section: Resultssupporting
confidence: 79%
“…Genetic variation is fundamental to successful breeding programs in vegetatively and sexually propagated plants (Olawuyi et al, 2015;Agbolade et al, 2016). This variation which occurs naturally or artificially induced by physical, biological or chemical mutagens has attracted the interest of plant breeders for many decades.…”
Section: Introductionmentioning
confidence: 99%
“…Significant variation in plant height may be due to the stress treatment encountered by plants before the occurrence of rainfall. Olawuyi et al, (2015) has reported the positive correlation between plant height and drought stress supporting our observations. The rainfall which occurred during the reproductive stage may have caused the plants to adapt to drought stress and resulted in recovery of yield and other yield parameters (Chen et al, 2016).…”
Section: Resultssupporting
confidence: 91%